Irish Information Society Policy - Conor Mc Caffery (Netcom)
The information sector has been a key contributor to the development of Ireland in the relatively recent past. The primary focus of Irish ICT related policy was on economic and educational aspects in order to maximise the country’s competitiveness within the global market. In more recent years the government has made a concerted effort to build upon this foundation, specifically to promote a knowledge-based society and address issues relating to digital inclusion (eInclusion). This paper, presenting key documents, traces the evolution of Irish information-society policy since it first emerged. Then the current policy framework at national, regional and local levels is outlined before implementation actions are traced. Also brought into consideration is the interaction between central governance and the key regional, county and community actors. Ireland’s performance as a European information society is benchmarked through a number of indicators in order to investigate how effective the policies have been. The paper closes with thoughts as to why Ireland is not performing as well as it could and how this might be addressed.